Why not uncivil disobedience?. Issue 7 (10th November 2022) - Scheuerman, William E.
ABSTRACT: An impressive body of recent literature posits that traditional notions of civil disobedience prevent us from properly considering potentially legitimate types of 'uncivil' political lawbreaking. When might uncivil (covert, legally evasive, morally offensive and potentially violent) lawbreaking prove normatively acceptable? If justifiable, what conditions should its practitioners be reasonably expected to meet? Despite some important insights, defenders of uncivil disobedience rely on a narrow and sometimes misleading view of civil disobedience, as previously practiced and theorized. Notwithstanding legitimate skepticism about Rawlsian notions of civil disobedience, they reproduce its troublesome binary or 'all-or-nothing' view of political lawbreaking. Uncivil disobedience's proponents tend to group a vast array of distinctive types of lawbreaking under one amorphous categorical rubric, impeding the suitably complex, nuanced analysis we need. A superior approach would pay careful attention to uncivil disobedience's ambivalent historical record, a record suggesting that UD is more likely to reproduce authoritarian populism's disturbing political logic than counteract it.